SYNTHESIS AND BIOLOGICAL STUDIES OF MN (II), CO (II), ZN (II) AND NI (II) COMPLEXES DERIVED FROM O, N DONOR SCHIFF BASE OF SULPHAMETHOXAZOLE. - V.UMA; SUNIL JOSHI; VATSALA PAWAR (International Journal of Pharma and Bio Sciences, 2010)
Two new respectively Schiff bases were prepared by taking p-Chlorobenzaldehyde and Vanillin with Sulphamethoxazole.The complexes of the type MPbS, MVS were prepared further and all were characterized on the basis of elemental analysis, IR spectra, 1HNMR spectra, conductivity, Melting Point and Molecular Weight determination. Comparative biocidal behavior of Schiff bases and their metal complexes have also been studied against Gram (-) like E. coli and Gram (+) like S. aureus, M. luteus and B. lichenformis (ATCC).